Current problems of postoperative radiotherapy for non-small cell lung cancer - S. D. Trotsenko; V. M. Sotnikov; G. A. Pan’shin; V. D. Chkhikvadze (Вестник рентгенологии и радиологии, 2016)
The review considers the history of evolution and the present state of the problem of postoperative radiotherapy for non-small cell lung cancer. The randomized trials and meta-analyses given in recent publications provide evidence that it should be usedin radically operated patients with morphologically verified regional metastases. The paper also shows promises of hypofractionation and a postoperative radiation/chemotherapy ratio for non-small cell lung cancer.